SAPA (School Health Program) and Breathing Exercises for Children at SDN 06 Pontianak Timur - Wahyuni, Tri; Jiu, Cau Kim; Ariyanti, Sri; Surtikanti (Pascasarjana Universitas Mataram, 2025)
Health education and socialization about preventing Acute Respiratory Tract Infection (ARTI) can increase public knowledge and awareness of the importance of clean and healthy living behavior. This activity helps the community understand how to prevent ARTI through simple actions such as washing hands, covering the mouth when coughing or sneezing, and maintaining environmental cleanliness. Furthermore, this community service can also provide other benefits, such as Increased knowledge. Through counseling and socialization, the community obtains information about ARTI, its causes, symptoms, and how to prevent it. Increased awareness, the community becomes more aware of the importance of maintaining their own health and the surrounding environment to prevent ARTI. When increased clean and healthy living behavior, the community begins to implement clean and healthy living behavior in everyday life, such as washing hands, covering the mouth when coughing or sneezing, and maintaining environmental cleanliness. Reducing the incidence of ARTI, with better knowledge and awareness, the community can reduce the risk of ARTI in themselves and their families. Community Empowerment, Through community service activities, the community is actively involved in efforts to prevent ARTI, so that they feel responsible for public health.